«Esa foto es la que más me ha gustado de él»1. Historias fotográficas familiares contadas por videollamadas - Figueroa Espejo, Mercedes (2023)
This article proposes methodological reflections on a digitally mediated ethnographic work that explores the family memories of police and military personnel killed in armed action during the Peruvian internal armedconflict (1980-2000). This exploration was carried out through the consultation of their domestic photographic archives (analog and digital) and from the voices of their closest relatives (widows and older sister). Thus, it was proposed to make visible other stories in relation to the violence of those years. The research digital mediation was held mainly through WhatsApp video calls. This social network allowed the conduction of interviews and photo elicitation exercises with analog photographs, to reconstruct lifestories. This experience encouraged a series of (re)adaptations and (re) learnings to understand these video calls as ethnographic meeting places and as windows into the everyday and intimacy of homes, inviting to rethink distances and places of enunciation in research contexts.